Optimization of adult sensory neuron electroporation to study mechanisms of neurite growth - McCall, Julianne Rose; Nicholson, LaShae; Weidner, Norbert; Blesch, Armin (Frontiers in molecular neuroscience, 2012)
The development of eukaryotic transfection technologies has been rapid in recent years, providing the opportunity to better analyze cell-autonomous mechanisms influencing various cellular processes, including cell-intrinsic regulators of regenerative neurite growth and survival. Electroporation is one of the more effective methodologies for transfection of post-mitotic neurons demonstrating sufficient neuronal survival and transfection efficiency. To further maximize the number of transfected neurons especially with large plasmids, to limit the cellular exposure to serum, and to minimize the number of animals required for cell isolation per experiment, we compared two state-of-the-art electroporation devices for in vitro transfection of adult rat dorsal root ganglion (DRG) neuron cultures. By refining different parameters, transfection efficiencies of 35-40% of adult DRG neurons could be achieved using the Lonza 4D-Nucleofector X-unit system, 1.5-2-fold higher rates than those that have been previously published using smaller plasmid sizes. Our protocol further limits the number of cells required to 3 x 10e5 cells per 20 µl reaction using only 2 µg DNA/reaction and allows for the complete omission of serum post-transfection. This method can also be adapted to embryonic DRG neurons and postnatal cerebellar granule neurons. Application of this optimized protocol will contribute to furthering the study of neuronal intrinsic mechanisms responsible for growth and survival under physiological and pathophysiological conditions.